PENDIDIKAN ISLAM TRADISIONAL DI LANGGHAR AL-HIDAYAH DAN LANGGHAR AL-IKHWAN ORAY PAMAROH KADUR PAMEKASAN - Zainal Abidin (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2018)
Langghar as two non-formal education institutions deserves to be maintained and developed. Among the aspects that need to be maintained is the method of traditional Islamic education in Langghar in order to always instill Islamic values from an early age. Whereas among the aspects that need to be developed are facilities and infrastructure so that the implementation of Islamic education in Langghar continues. The results show that: first, the method used in Langghar al-Hidayah is a collaborative method. The method used in Langghar al-Ikhwan is a traditional method. Second, the reason Langghar al-Hidayah still maintains the method because it is able to instill Islamic values in the santri, while the reason for the Langghar al-Ikhwan is because the method is able to educate students to memorize the basics of aqeedah, fiqh and morals. While the inhibiting factors are the same, namely the santri stops or is lazy to recite when he wants to continue his education to junior high school, the level of delinquency of the santri and the intelligence of the different santri. While the supporting factors are in Langgharal-Hidayah, namely the teacher's experience and the book used. Whereas in Langghar al-Ikhwan, there is a free teacher experience.[Langghar sebagai dua lembaga pendidikan nonformal layak untuk dipertahankan dan dikembangkan. Di antara aspek yang perlu dipertahankan adalah metode pendidikan Islam tradisional di Langghar agar senantiasa menanamkan nilai-nilai keislaman sejak dini. Sedangkan di antara aspek yang perlu dikembangkan adalah sarana dan prasarana agar pelaksanaan pendidikan Islam di Langghar tetap berjalan. Hasil penelitian menunjukkan bahwa: pertama, metode yang digunakan di Langghar al-Hidayah adalah metode kolaboratif. Adapun metode yang digunakan di Langghar al-Ikhwan adalah metode tradisional. Kedua, alasan Langghar al-Hidayah tetap mempertahankan metode tersebut karena mampu menanamkan nila-nilai keislaman dalam diri santri, sedangkan alasan Langghar al-Ikhwan karena metode tersebut mampu mendidik santri menghafal dasar-dasar akidah, fikih dan akhlak. Sedangkan faktor penghambatnya sama, yaitu santri berhenti atau malas mengaji ketika sudah mau melanjutkan pendidikan ke SMP, tingkat kenakalan santri dan kecerdasan santri yang berbeda. Sedangkan faktor pendukungnya yaitu kalau di Langgharal-Hidayah yaitu pengalaman guru dan kitab yang digunakan. Sedangkan di Langghar al-Ikhwan yaitu pengalaman gurudan gratis]